2019
DOI: 10.1002/wsbm.1459
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic simulation algorithms for computational systems biology: Exact, approximate, and hybrid methods

Abstract: Nowadays, mathematical modeling is playing a key role in many different research fields. In the context of system biology, mathematical models and their associated computer simulations constitute essential tools of investigation. Among the others, they provide a way to systematically analyze systems perturbations, develop hypotheses to guide the design of new experimental tests, and ultimately assess the suitability of specific molecules as novel therapeutic targets. To these purposes, stochastic simulation al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 92 publications
(164 reference statements)
0
10
0
Order By: Relevance
“…Once a subset of parameters are identified that can be fitted, a number of optimization approaches can be deployed to identify an appropriate fit. In this section, we discuss the importance and need for evolving technology and methodological advances that are necessary to improve on the capability of QSP model optimization to clinical or preclinical data, as well as simulation strategies (Marchetti et al, 2017;Simoni et al, 2019a).…”
Section: Model Calibration and Analysis: Evolving Technology And Methmentioning
confidence: 99%
“…Once a subset of parameters are identified that can be fitted, a number of optimization approaches can be deployed to identify an appropriate fit. In this section, we discuss the importance and need for evolving technology and methodological advances that are necessary to improve on the capability of QSP model optimization to clinical or preclinical data, as well as simulation strategies (Marchetti et al, 2017;Simoni et al, 2019a).…”
Section: Model Calibration and Analysis: Evolving Technology And Methmentioning
confidence: 99%
“…While analytical solutions can be found only for very simple CMEs, these can be solved by common numerical methods. More frequently, as CMEs represent probability distributions, they are analyzed by the so-called stochastic simulation algorithms (SSAs), such as the Gillespie algorithm and several of its approximations [ 130 , 131 ].…”
Section: Mechanistic Modelsmentioning
confidence: 99%
“…CTLs are described by the Eq. (12). The action of D f cells activates CTLs, as defined by the "activaton by D f " term, and IL-2 promotes their proliferation, as described in the "stimulation by IL-2" term.…”
Section: CXmentioning
confidence: 99%
“…Mathematical modeling has been successfully applied in the context of computational systems biology to develop comprehensive mathematical descriptions of several pathologies [1][2][3][4][5][6][7][8][9] . Mathematical models are calibrated through experimental data to simulate in silico biological systems and test hypotheses, for example regarding the regulative mechanisms of complex diseases [10][11][12][13][14][15][16] . Quantitative system pharmacology (QSP) is a popular modeling approach that supports the pharmaceutical industry in validating or identifying drug targets, designing new therapies and evaluating side effects [17][18][19][20][21] .…”
mentioning
confidence: 99%